DIGITAL TECHNOLOGIES IN AGRICULTURAL PRODUCTION MANAGEMENT: ECONOMIC AND ENVIRONMENTAL ASPECTS - CHERNIKOVA, Nataliia; SATSIUK, Yulia; KHALIAVA, Vadym; LELIUKH, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the role of digital technologies in agribusiness management, proves the relevance of this issue for agricultural enterprises at the current stage, as they allow to simultaneously optimize costs, increase productivity and reduce the impact on the environment. It has been established that digital technologies are an important tool for managing the efficiency and competitiveness of agricultural enterprises, as well as achieving high environmental results of their activities. The digital technologies that are most popular in agriculture today are identified, namely: precision farming systems, drones and aerial photography, the Internet of Things for agriculture, artificial intelligence and satellite monitoring, farm management systems, Big Data and analytics, blockchain for tracking supply chains, etc. The economic and environmental effects of the use of these technologies have been established. Among the economic advantages should be included the reduction of costs for resource provision of enterprise activities, increase in productivity, improvement of interaction with clients and increase in the level of income. The ecological effect is achieved due to the transition to frugal production and preservation of natural resources and biodiversity, optimization of the use of land resources, improvement of soil conditions, compliance with international environmental standards, etc. The experience of foreign countries in the use of digital technologies in agricultural production is presented, as well as the leading domestic companies in terms of the level of digitalization of all business processes, the main directions and advantages of their use of modern technologies. t has been proven that the use of digital solutions in agricultural production is an important direction of sustainable development, combining economic benefit with environmental responsibility, contributing to ensuring global food security. A conclusion was made about the need for further research in the direction of identifying the problems that cause the agricultural industry to lag behind in the use of digital technologies in the agricultural sector compared to other spheres and branches of activity, as well as finding ways to solve them.